Implementasi Pidana Pokok Pelatihan Kerja terhadap Anak Pelaku Tindak Pidana Narkotika di Kabupaten Kuningan - Fauzan, Abel Capan; Hidayat, Sarip; Andriyani, Yani; Akmaddhian, Suwari (Universitas Kuningan, 2024)
The basic crime of job training is a form of sanction for children in the form of actions aimed at protecting children in the future. The aim is to find out how the laws and regulations regulate the basic punishment for job training for children who commit narcotics crimes in Indonesia and to find out how the basic punishment for job training for children who commit narcotics crimes in Kuningan district is implemented. Study at the Griya Bina Karsa Cileungsi Social Service Center Bogor Regency. This research method uses empirical juridical and the location is the Griya Bina Karsa Cileungsi Social Service Center, Bogor Regency (PPSBGK). The results of this research are that there are 2 (two) regulations that regulate the basic crime of job training, namely Article 71 (1) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Article 4 of Government Regulation No. 58 of 2022 concerning Forms and Procedures for Implementing Crimes and Actions Against Children. The conclusion of this research is that the regulations governing the principal criminal punishment for job training for children who commit narcotics crimes are Article 71 (1) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Article 4 of Government Regulation No. 58 of 2022 concerning Forms and Procedures for the Implementation of Crimes and Actions Against Children and the implementation of basic criminal penalties for job training at the Griya Bina Karsa Cileungsi Social Service Center, Bogor Regency have been implemented well. Suggestions are for institutions that make laws and regulations to make regulations clearer regarding what type of job training must be carried out by children who commit criminal acts and for the Griya Bina Karsa Cileungsi Social Service Center, Bogor Regency, to monitor the results of coaching periodically so that the children's development results are monitored.